More than a look into a crystal ball: protein structure elucidation guided by molecular dynamics simulations. Issue 11 (November 2016) - Bermudez, Marcel; Mortier, Jeremie; Rakers, Christin; Sydow, Dominique; Wolber, Gerhard
Graphical abstract: Highlights: Considering conformational flexibility improves structure-based drug design. Computational simulations provide mechanistic insights in biological processes. Enhanced sampling algorithms allow the investigation of large biological systems. Molecular dynamics simulations enable mechanistic investigations of protein folding. Abstract : The 'form follows function' principle implies that a structural determination of protein structures is indispensable to understand proteins in their biological roles. However, experimental methods still show shortcomings in the description of the dynamic properties of proteins. Therefore, molecular dynamics (MD) simulations represent an essential tool for structural biology to investigate proteins as flexible and dynamic entities. Here, we will give an overview on the impact of MD simulations on structural investigations, including studies that aim at a prediction of protein-folding pathways, protein-assembly processes and the sampling of conformational space by computational means.